EutherianCoP. An integrated biotic and climate database for conservation paleobiology based on eutherian mammals - Alessandro Mondanaro; Giorgia Girardi; Silvia Castiglione; Axel Timmermann; Elke Zeller; Thushara Venugopal; Carmela Serio; Marina Melchionna; Antonella Esposito; Mirko Di Febbraro; Pasquale Raia (Scientific Data)
Abstract We present a new database, EutherianCoP, of fossil mammals which lived globally from the Late Pleistocene to the Holocene. The database includes 13,972 fossil occurrences of 786 extant or recently extinct placental mammal species, plus 155,198 current occurrences for those of them which survived to the present. The occurrences are correlated with radiometric age information. For all species, we provide 32 different traits, inclusive of taxonomic, phenotypic, life history, biogeographic and phylogenetic information. Differently from any other compilation, the occurrences are complemented with estimates of past climatic conditions, including site-interpolated monthly and annual precipitation and temperature, leaf area index, megabiome type and net primary productivity, which are derived from transient paleo model simulations conducted with the Community Earth System Model 1.2 and the BIOME4 vegetation model. All data are further downloadable for further investigation.